Characteristics of the Recirculation Sector of Finfish Aquaculture in the United States and Canada - Delabbio, Juliette L.; Murphy, Brian R.; Johnson, G. R.; Hallerman, Eric M. (International Journal of Recirculating Aquaculture, 2003)
In the autumn of 2001, a survey was conducted to examine basic farm production and human resource characteristics of recirculation facilities in the United States and Canada currently growing finfish. An 86% response rate was achieved. The survey data indicate that this sector of aquaculture is quite heterogeneous. The number and pounds of fish produced is quite variable, with presence of small-, medium- and large sized farms in this sector. Recirculation technologies are employed to culture a wide variety of both warmwater and coldwater fishes in both saltwater and freshwater situations. The four fishes most commonly grown in recirculation units in the United States and Canada are Atlantic salmon smolts, tilapia, hybrid striped bass and ornamental fishes. A high proportion of facilities using recirculation technologies use pumped groundwater as a primary water source. Over 40% of facilities represented in the survey rely on a single water source to sustain their operation and have no secondary water source as backup. Management personnel of recirculation facilities are highly educated; more than 74% of respondents reported holding at least an undergraduate degree. The majority of personnel managing recirculation facilities are middle-aged individuals who have over 10 years of related work experience. The findings of this study represent the first empirical description of the recirculation sector of finfish aquaculture in the United States and Canada.